GAMBARAN TELUR CACING Oxyuris vermicularis PADA ANAK DI WILAYAH PESISIR PANTAI MERPATI BULUKUMBA - Andi Harmawati Novriani. HS (Akademi Kesehatan John Paul II Pekanbaru, 2023)
Helminthiasis is a public health problem in Indonesia. Oxyuriasis is an infectious disease caused by Oxyuris vermicularis (Enterobius vermicularis) or pinworms and is a non-STH (non-Soil Transmitted Helminth) intestinal worm that can move from one individual to another without the need for transmission through the soil and is widespread in children and toddlers. Objective: This study aims to determine the picture of Enterobius vermicularis worm eggs in children aged 3-8 years in coastal areas. Methods: This research is descriptive using a purposive sampling technique. The population in this study was 20 samples. The sampling method used the anal swab method which is the best method in diagnosing Oxyuris vermicularis. Worm eggs are taken with an anal swab or cellophane swab attached around the anus in the morning before the child does activities such as defecating, urinating, and bathing. Results: out of 20 samples, 3 samples were infected with Enterobius vermicularis eggs and 17 samples were negative. Enterobiasis cases in coastal areas are still high. Conclusion: Based on the results of Enterobius vermicularis worm eggs research, found in children aged 3-8 years, out of 20 samples found 3 samples were infected with Enterobius vermicularis worm eggs and 17 samples were negative Enterobius worm eggs. Where Enterobius vermicularis cases are still high in coastal areas.